The Design of Internal Control and Capital Structure - Berkovitch, Elazar; Israel, Ronen (Review of Financial Studies, 1996)
We study the design of internal control and capital structure. We pose the question, When is control allocated only to shareholders and when is it allocated to other stakeholders, such as debtholders, or the management team? We show that shareholders (debtholders) get control when the firm’s cash flow is relatively sensitive (insensitive) to managerial effort. Our theory implies that the signs of the correlations between endogenous variables when shareholders have absolute control are reversed when debtholders have veto power. In particular, debt level and firm value are negatively (positively) correlated when debtholders have veto power (shareholders have absolute control).